2018
DOI: 10.1097/aud.0000000000000518
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Correlates of Binaural Temporal Processing Deficits in Older Adults

Abstract: These results demonstrate an age-related decline in the processing of binaural temporal fine-structure cues with preserved temporal envelope coding that was similar with and without mild-to-moderate peripheral hearing loss. Such age-related changes can be reliably indexed by both behavioral and CAEP measures in young and older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
5
23
1
Order By: Relevance
“…The current results did not show any effect of hearing sensitivity on the IPM-FR or the binaural FM detection measures. Previous studies have not shown significant effects of high-frequency hearing sensitivity on low-frequency IPD discrimination using a variety of behavioral measures (Strelcyk and Dau, 2009;Grose and Mamo, 2012b;Moore et al, 2012;Eddins and Eddins, 2018), which is consistent with the current results. However, Vercammen et al (2018) did show that hearing sensitivity impacted the neural encoding of IPDs as measured by IPM-FRs elicited by a 492-Hz carrier tone, even after presentation levels were adjusted for audibility.…”
Section: Effects Of Age and Hearing Sensitivity On Binaural Processingsupporting
confidence: 92%
See 2 more Smart Citations
“…The current results did not show any effect of hearing sensitivity on the IPM-FR or the binaural FM detection measures. Previous studies have not shown significant effects of high-frequency hearing sensitivity on low-frequency IPD discrimination using a variety of behavioral measures (Strelcyk and Dau, 2009;Grose and Mamo, 2012b;Moore et al, 2012;Eddins and Eddins, 2018), which is consistent with the current results. However, Vercammen et al (2018) did show that hearing sensitivity impacted the neural encoding of IPDs as measured by IPM-FRs elicited by a 492-Hz carrier tone, even after presentation levels were adjusted for audibility.…”
Section: Effects Of Age and Hearing Sensitivity On Binaural Processingsupporting
confidence: 92%
“…This study showed that age had a significant effect on IPM-FR magnitude and SNR. These findings are consistent with previous work (Vercammen et al, 2018) and provide additional evidence that age can impact the neural encoding of IPD cues (Ross et al, 2007a;Grose and Mamo, 2012a;Ozmeral et al, 2016;Papesh et al, 2017;Eddins and Eddins, 2018;Ungan et al, 2020). The IPM-FR is measured in response to IPD cues from temporal fine structure differences in an ongoing stimulus and is likely impacted by deficits in the extraction and integration of IPD information at the level of the brainstem.…”
Section: Effects Of Age and Hearing Sensitivity On Binaural Processingsupporting
confidence: 89%
See 1 more Smart Citation
“…The variability across subjects in that study, however, was so great that they separated listeners into two groups—one with “large” BMLDs (approximately 18 dB) and one with “small” BMLDs (approximately 10 dB). BMLDs in the current study are closer to the small BMLD group of D. A. Eddins and Barber, whereas BMLDs in the A. C. Eddins and Eddins (2018) study are closer to the larger BMLD group of D. A. Eddins and Barber's study.…”
Section: Methodssupporting
confidence: 50%
“…In these situations, the listener primarily relies on their binaural system to detect and process the cues necessary to determine the spatial location of the speech as well as cues to help segregate speech from the background competition. Unfortunately, known age-related declines in high-frequency hearing sensitivity (e.g., Allen & Eddins, 2010; Cruickshanks, Wiley, Tweed, Klein, Klein, Mares-Perlman, & Nondahl, 1998) and in the ability to process important monaural and binaural temporal fine structure and envelope features (Eddins & Eddins, 2017; Gallun et al, 2014; Gordon-Salant & Fitzgibbons, 1999; Grose & Mamo, 2010; Hopkins & Moore, 2009; Ozmeral, Eddins, Frisina, & Eddins, 2016) can have a significant impact on the ability of older adults to effectively access and use the cues needed for perception of auditory space and speech understanding in background competition.…”
Section: Introductionmentioning
confidence: 99%